Madrid the history - Stewart, Jules (I.B. Tauris, 2012)
At the heart of the Castilian plateau, far from the seething coastal resorts of Spain, sits the great city of Madrid. Perched some 2,200 feet above the distant sea, it is at once the loftiest and also the most enigmatic of Europe's capitals: difficult to understand for the Spanish and foreigners alike. Its intense character and the abrupt manner and hectic lifestyle of the madrileños can make even other Spaniards feel exhausted. Yet Madrid has a rich historical and cultural life which attracts almost eight million visitors per year, drawn to its beautiful palaces and churches, the magnificent collections of the Prado, and the pervasive echoes of a faded empire. Despite its ancient origins, Madrid feels like a modern, youthful city. But the legacy of Madrid's "golden age"--the Spanish colonies from the Andes to the Philippines from which the city derived its wealth--remains evident in the extravagant Baroque façades of the old city. Jules Stewart here provides an insider's account of Madrid and unveils the history and culture of one of Europe's most fascinating, but least understood cities.